2019
DOI: 10.1519/jsc.0000000000002811
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation During Power-Oriented Resistance Training: Continuous vs. Cluster Set Configurations

Abstract: Morales-Artacho, AJ, García-Ramos, A, Pérez-Castilla, A, Padial, P, Gomez, AM, Peinado, AM, Pérez-Córdoba, JL, and Feriche, B. Muscle activation during power-oriented resistance training: continuous vs. cluster set configurations. J Strength Cond Res 33(7S): S95–S102, 2019—This study examined performance and electromyography (EMG) changes during a power training protocol comprising continuous or clustered set configurations. Eighteen active males completed 6 sets of 6 repetitions during the loaded (20% 1 repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Likewise, recording electromyography (EMG) activity (amplitude, through root mean square “RMS,” and frequency, through median frequency “MDF”) may provide a better understanding of the mechanisms behind the changes in mechanical performance, such as muscle activation and neuromuscular fatigue accumulated throughout the training session (6). To date, only one previous study has examined neuromuscular activity during different set configurations involving lower-body muscles (25), which compared 6 sets of 6 repetitions at 20% of 1 repetition maximum (1RM) in loaded jumps, continuously ( n = 9) or with a 30-second rest every 2 repetitions ( n = 9). These authors observed larger increments in RMS throughout longer set configurations; however, both protocols induced similar decrements in MDF (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, recording electromyography (EMG) activity (amplitude, through root mean square “RMS,” and frequency, through median frequency “MDF”) may provide a better understanding of the mechanisms behind the changes in mechanical performance, such as muscle activation and neuromuscular fatigue accumulated throughout the training session (6). To date, only one previous study has examined neuromuscular activity during different set configurations involving lower-body muscles (25), which compared 6 sets of 6 repetitions at 20% of 1 repetition maximum (1RM) in loaded jumps, continuously ( n = 9) or with a 30-second rest every 2 repetitions ( n = 9). These authors observed larger increments in RMS throughout longer set configurations; however, both protocols induced similar decrements in MDF (25).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one previous study has examined neuromuscular activity during different set configurations involving lower-body muscles (25), which compared 6 sets of 6 repetitions at 20% of 1 repetition maximum (1RM) in loaded jumps, continuously ( n = 9) or with a 30-second rest every 2 repetitions ( n = 9). These authors observed larger increments in RMS throughout longer set configurations; however, both protocols induced similar decrements in MDF (25). However, the fact that different subjects performed each protocol may have obscured potential differences in the EMG spectral parameters between protocols.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, monitoring the electromyography (EMG) activity attained in each repetition may provide better knowledge about the muscle excitation and neuromuscular fatigue accumulated throughout the training session (44). To the best of our knowledge, only one study has investigated the effect of CS configuration on EMG activity (27), by comparing 6 sets of 6 repetitions at 20% of 1RM in the loaded countermovement jump (CMJ) exercise, continuously or with a 30-second pause every 2 repetitions (27). These authors observed a greater root mean square (RMS) in the vastus lateralis and rectus femoris muscles, but not in the vastus medialis, during the TRD configuration compared with a CS, along with progressive decrements in median frequency (MDF) without differences between set configurations (27).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one study has investigated the effect of CS configuration on EMG activity (27), by comparing 6 sets of 6 repetitions at 20% of 1RM in the loaded countermovement jump (CMJ) exercise, continuously or with a 30-second pause every 2 repetitions (27). These authors observed a greater root mean square (RMS) in the vastus lateralis and rectus femoris muscles, but not in the vastus medialis, during the TRD configuration compared with a CS, along with progressive decrements in median frequency (MDF) without differences between set configurations (27). Likewise, the CMJ exercise involves both eccentric and concentric muscle actions, whereas the CS approach is mainly used to maintain acute concentric exercise performance (39).…”
Section: Introductionmentioning
confidence: 99%
“…Participants self-selected their walking speed (SS) during a five-minute trial on the instrumented treadmill (Bertec, Columbus, OH, USA, 1000 Hz). Based on a previously established cross-correlation approach, the measured signals (IMUs and GRF) were synchronized in pre-processing [ 46 ]. The walking at three speeds was recorded: SS, 20% faster and slower than SS.…”
Section: Methodsmentioning
confidence: 99%